Revision of the genus Bioramix Bates, 1879 (Coleoptera: Tenebrionidae: Platyscelidini) from China - Bai, Xing-Long; Ren, Guo-Dong (Zootaxa, 2020)
The genus Bioramix Bates, 1879 from China is revised, 54 valid species are recognized in this study, including 23 new ones: B. (Cardiobioramix) barkamica sp. nov., B. (C.) gibbosa sp. nov., B. (C.) longicornis sp. nov., B. (C.) prolongata sp. nov., B. (C.) tenuitarsus sp. nov., B. (Leipopleura) baxoica sp. nov., B. (L.) cupreoviridis sp. nov., B. (L.) exsertigenae sp. nov., B. (L.) homoplasta sp. nov., B. (L.) impressithorax sp. nov., B. (L.) latitarsis sp. nov., B. (L.) laxipenis sp. nov., B. (L.) lhozhagensis sp. nov., B. (L.) longipilis sp. nov., B. (L.) miranda sp. nov., B. (L.) nigra sp. nov., B. (L.) rectiangulata sp. nov., B. (L.) riwoqeica sp. nov., B. (L.) rugelytra sp. nov., B. (L.) seidlitzi sp. nov., B. (L.) subcarinata sp. nov., B. (L.) tiani sp. nov., B. (L.) yushuana sp. nov. The following new synonymy is proposed based on the examination of type and additional specimens: B. (C.) globipunctata Bai & Ren, 2016 = B. (C.) liupanshana Bai & Ren, 2016, syn. n.; B. (C.) szetschuana (Kaszab, 1940) = Platynoscelis (C.) kulzeri Kaszab, 1960, syn. n.; B. (L.) integra (Reitter, 1887) = Platyscelis (Platyscelis) obovatus Ren, 1999, syn. n.; B. (L.) politicollis (Kaszab, 1940) = B. (L.) baqenensis Li & Egorov, 2016, syn. n.; B. (L.) rubripes (Reitter, 1889) = Myatis brevipilosum Meng & Ren, 2005, syn. n., formerly synonymized with B. (L.) micans Reitter, 1889; B. (L.) rufipalpis (Reitter, 1887) = Platynoscelis (Trichoplatyscelis) darbukensis Kaszab, 1940, syn. n. The subgenus Planoplatyscelis Kaszab, 1940 and B. (P.) pamirensis Bates, 1879 are recorded from China for the first time. Lectotypes are designated for Helops subaenea Reitter, 1889 and Botiras punctatellus Fairmaire, 1891. The biology of adult, larvae and pupa is briefly introduced. Furthermore, new distribution records, images of adults, male aedeagus and habitat, and a key to Chinese species are presented.